The Implementation of Peer Tutoring as a Teaching Method in Banten to Enhance Students' Reading Comprehension of Narrative Text - Syafrizal Syafrizal; Tosi Rut Syamsun (Journal of Linguistics, Literacy, and Pedagogy, 2023)
Detecting objects, text structures, important concepts, vocabulary errors, and other reading-related challenges are all improved by this instruction for Banten students. The researchers decided to use this topic in order to demonstrate the success of a strategy used to counteract pupils who were careful about reading while still achieving the goal of the study was to check out some Banten students’ narratives and to verify the expectations outlined in the earlier research. researchers employed research methodologies with quantitative methods within the test project. In the first session, the test group consisted of 16 out of the 32 social studies students in the sample and 16 were in the control group. The data was collected by pre-checking and post-testing, and Independent-Sample T-test while being subjected to the selection test known as the test. It was clear from the inquiry that the peer tutoring technique improved learners' reading concepts or comprehension of narrative texts. This is supported by the Independent Sample T-Test post-test findings. According to the results, H° is rejected while Ha is approved since the quantity of Sig (2-tailed) is 0.045, which indicates that the quantity is less than 0.05. This illustrates that employing peer tutoring has both a major impact and a substantial result.